Combination of fenton oxidation and composting for the treatment of the olive solid residue and the olive mile wastewater from the olive oil industry in Cyprus - Zorpas, Antonis A.; Costa, Costas (My University, 2010)
Co-composting of olive oil solid residue (OOSR) and treated wastewaters (with Fenton) from the olive oil production process has been studied as an alternative method for the treatment of wastewater containing high organic and toxic pollutants in small olive oil industry in Cyprus. The experimental results indicated that the olive mill wastewater (OMW) is detoxified at the end of Fenton Process and the COD is reduced up to 70%. The final co-composted material of OOSR with the treated olive mile wastewater (TOMW) is presented with optimum characteristics and is suitable for agricultural purpose. The final product coming out from an in-Vessel reactor seems to mature faster than the product from the windrow system and is presented with a better soil conditioner.
Keywords: Compost; Olive mill wastewater; Fenton; Olive oil solid residue